2023
DOI: 10.1186/s40634-023-00580-5
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted analysis of functional internal rotation after reverse total shoulder arthroplasty: implications for component choice and orientation

Abstract: Purpose Functional internal rotation (IR) is a combination of extension and IR. It is clinically often limited after reverse total shoulder arthroplasty (RTSA) either due to loss of extension or IR in extension. It was the purpose of this study to determine the ideal in-vitro combination of glenoid and humeral components to achieve impingement-free functional IR. Methods RTSA components were virtually implanted into a normal scapula (previously est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Our results show that the internal rotation is satisfactory when the humeral component is placed in 30° of retroversion in most cases. A recent computer-assisted study by Hochreiter et al reported the ideal component placements in order to obtain the best range of motion in internal rotation; the largest impingement-free functional internal rotation was achieved when combining a posteroinferior baseplate position, a greater inferior glenosphere overhang, a baseplate inclination angle of 90°, 6 mm of glenosphere lateralisation with respect to the baseline setup, a lower NSA and anteversion of the humeral component [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the internal rotation is satisfactory when the humeral component is placed in 30° of retroversion in most cases. A recent computer-assisted study by Hochreiter et al reported the ideal component placements in order to obtain the best range of motion in internal rotation; the largest impingement-free functional internal rotation was achieved when combining a posteroinferior baseplate position, a greater inferior glenosphere overhang, a baseplate inclination angle of 90°, 6 mm of glenosphere lateralisation with respect to the baseline setup, a lower NSA and anteversion of the humeral component [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, these features affect the acromion's efficacy as a posterior restraint of the humerus during glenohumeral elevation. Correction of the combined anomalies experimentally restores normal posterior translation of the humerus on elevation of the arm 23 . Our case is in agreement with the experimental data and documents that correction of scapular anatomy can restore normal glenohumeral congruity in SPSL in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of promising alternatives and with the consistent and specific observation of abnormal scapular anatomy 10,21,22 as well as the biomechanical documentation that posterior escape can experimentally be prevented by scapular correction 23 , we performed a "SCOPE" (scapular (acromion and glenoid) corrective osteotomy for posterior escape) procedure in a patient with symptomatic SPSL with mild degenerative changes and report the outcome at 2 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, 3D bone models were extracted from the CT data (Siemens SOMATOM Definition AS, Siemens Healthcare, Erlangen, Germany) using a commercial segmentation software (Mimics 19.0; Materialise NV, Leuven, Belgium) 25 27 . The 3D models were then imported into a planning software (CASPA; Balgrist CARD, Zurich, Switzerland) including the reconstruction template.…”
Section: Methodsmentioning
confidence: 99%